2009
DOI: 10.1017/s1368980009990280
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of severe iodine-deficiency disorders despite universal salt iodization in an iodine-deficient area in northern India

Abstract: Objective: The aim of the present study was to determine the impact of universal salt iodization (USI) on the prevalence of iodine deficiency in the population of an area previously known to have severe iodine deficiency in India. Design: In a cross-sectional survey, a total of 2860 subjects residing in fifty-three villages of four sub-districts of Gonda District were examined for goitre and urinary iodine concentration. Free thyroxine and thyroid-stimulating hormone levels were also measured. Salt samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…But with the use of iodized salt, the prevalence of goitre has decreased. 8 In our study we found around 85% of patients using iodized salt as seen in Figure 2. According to a study thyroid disorder are 8 times more common in females than males.…”
Section: Discussionsupporting
confidence: 47%
“…But with the use of iodized salt, the prevalence of goitre has decreased. 8 In our study we found around 85% of patients using iodized salt as seen in Figure 2. According to a study thyroid disorder are 8 times more common in females than males.…”
Section: Discussionsupporting
confidence: 47%
“…There was a decline of goitre prevalence from 23% to 15·5% when compared with our previous nationwide study 9 conducted a decade earlier. Other regional studies from India have also reported a residual goitre prevalence of 15·1–37·6% 10,18–21 . An impressive decline of goitre prevalence from 49·9% to 6·2% was reported from Bangladesh after one decade of iodization despite persistence of iodine deficiency in one‐third of their study population 8 and 25–6·9% from Tanzania 7 after one decades of salt iodization.…”
Section: Discussionmentioning
confidence: 81%
“…Other regional studies from India have also reported a residual goitre prevalence of 15AE1-37AE6%. 10,[18][19][20][21] An impressive decline of goitre prevalence from 49AE9% to 6AE2% was reported from Bangladesh after one decade of iodization despite persistence of iodine deficiency in one-third of their study population 8 and 25-6AE9% from Tanzania 7 after one decades of salt iodization. However, persistence of endemic goitre after salt iodization ranging from 10AE4% to 39AE6% has been reported by several authors from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted to the launching of the USI (Universal Salt Iodization) program, an exceptional cost effective community health intervention strategy [53]. This program recorded remarkable success worldwide in reducing the incidence of thyroid disease [54,55,56].…”
Section: Discussionmentioning
confidence: 99%